The art of non-verbal communication in perlocutionary giftedness - Adam Świątek (LingBaW)
Language aptitude and perlocutionary acts and effects have been subjects of extensive research since their true beginnings in the 1950’s and 1960’s, respectively. On the one hand, Carroll and Sapon (1959), Pimsleur (1966), or Biedroń (2012) aimed at revealing the factors responsible for a learner’s sixth sense for languages. On the other hand, almost simultaneously, Austin (1962) introduced the tripartite division of a speech act, with locutions, illocutions, and perlocutions as the integral components, later developed by Searle (1969), who shed new light on the Speech Act Theory (SAT). At that time, however, the role of the perlocutionary component was significantly diminished, since the primary goal of pragmatics was to investigate the speaker’s intentions. Gradually, the role of perlocutionary acts and effects changed and more attention was drawn to the perlocutionary aspect. In 1979, Cohen, Davis and Gaines highlighted the fact that perlocutionary acts have perlocutionary goals, which might be observed by the subsequent effects utterance have on the listener. In 2013, Post offered a new insight into the SAT and suggested that the role of perlocution ought not to be diminished, but enhanced and intensified. In 2015, Świątek suggested a contrasting approach to both concepts and combined them to investigate the role of individual differences responsible for one’s verbal perlocutionary giftedness. The research revealed that the aspects like verbal aptitude, anxiety, willingness to communicate, or personality type had considerable impact on perlocutionary skills and the desired perlocutionary effects. Świątek’s approach shed new light on the research on pragmatic aspects of glottodidactics and opened a new chapter in that field of science. The aim of the presentation is to concentrate on yet another fundamental factor of perlocutionary giftedness, i.e. non-verbal aspects in its manifestation. The research, based on experiential and comparative methods as well as individual case analysis, aimed at revealing a strong link between verbal perlocutionary giftedness and the accompanying non-verbal aspects of communication, such as kinesics, proxemics, vocalics, or posture, which affect the listener’s decisions, who then complies with the speaker’s will.